Membangun Brand Awareness Melalui Strategi Digital Marketing Di Kala Hotel Semarang - Syamsul Hadi; Ahmad Mansur; Umar Abdul Jabbar (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
In general, the development of a company is certainly inseparable from the Human Resources (HR) within it. There is a lot of history of a company being able to achieve extraordinary rapid development due to the professionalism of HR which is very well managed. This community service aims to 1) Increase knowledge and understanding of effective digital marketing strategies for HR at Kala Hotel Semarang. 2) Improve Kala Hotel Semarang's ability to manage digital platforms such as social media, websites and SEO and 3) Assist Human Resources or Kala Hotek employees in developing a comprehensive digital marketing strategy to increase brand awareness and reach market targets. So the result of this service is to open up insight to hotel HR about the importance of digital marketing in the industry by always contributing individually without coercion and being able to create interesting and effective social media content so that the media can become promotional material.